IMPROVING PEMPEK’S SHELF LIFE USING YAM’S STARCH BASED BIOPLASTICS PACKAGING WITH ADDITION OF CLOVE OIL - Ulyarti Ulyarti; Ria Amelia Yolanda; Dian Wulansari; Agus Salim; Nazarudin (Jurnal Teknologi Pertanian, 2023)
This study aimed to determine the effect of yam starch and clove oil based bioplastics packaging on the microbiological and sensory properties of pempek during storage. This research was carried out by using different packaging on pempek: bioplastics and polyethylene plastic. Pempek in each group was kept for 0, 8, 16, 24, 48 hours at room temperature. The total of Staphylococcus aureus bacteria was determined using colony forming unit and the sensory properties were obtained by the determination of color, texture and aroma of pempek using 5 skilled panelists. The results showed that the use of bioplastics packaging decreased the growth of Staphylococcus aureus bacteria in pempek compared to polyethylene plastics. The decrease in acidity was in line with the growth of Staphylococcus aureus that was steeper in pempek packaged with polyethylene plastics. The use of bioplastics also maintained the sensory properties of pempek (smell of damage) during storage better than the polyethylene plastic did.